Impacts of Renewable Energy Sources and Artificial Intelligence on Grid Reliability and Cost: A Case Study of Libya - Suleiman Abdulagadir M. Edreis; Mostafa Abubakar Mohmed Kaud; Abdussalam Mohamed Ali Altaher; Aimn Azoumi Mohammed; Massoud Ali Abdalhadi (African Journal of Advanced Pure and Applied Sciences, 2025)
Libya with its abundant solar and wind resources, stands at the forefront of renewable energy potential in North Africa. However, integrating these intermittent energy sources into the grid poses significant challenges, particularly regarding reliability and cost. This manuscript explores the dual role of renewable energy and artificial intelligence (AI) in addressing these challenges, focusing on Libya’s unique climatology. The study evaluates the technical, economic, and environmental impacts of renewable energy integration, supported by AI-driven solutions, and provides actionable recommendations for Libya’s energy transition.